Development of bisulfite-free DNA methylation sequencing methods and their application to cell-free DNA for cancer detection - Siejka-Zielinska, P (2020)
5-Methylcytosine (5mC) is the most abundant epigenetic mark in DNA regulating gene expression and influencing crucial cellular processes. Aberrant DNA methylation is involved in pathogenesis of human malignancies. Detection of cancer-specific methylation patterns in cell-free DNA (cfDNA) is a promising approach for development of minimally invasive, liquid biopsy assays. Most of methylation sequencing methods are based on bisulfite treatment that causes an extensive DNA damage, therefore are not ideal for analysis of minute amount of cfDNA. Unfortunately, technological limitations affect whole-genome methylation analysis of cfDNA. During the course of this project, we developed and validated novel approaches addressing the most important drawbacks of currently available technologies.